Organelle DNA variation and systematic relationships in the genus Zea: Teosinte - Timothy, D. H. (1979)
Chloroplast and mitochondrial DNAs from six races of annual teosinte (Guatemala, Huehuetenango, Balsas, Central Plateau, Chalco, and Nobogame), perennial teosinte, and maize were compared and grouped by restriction endonuclease fragment analyses. Three groups of chloroplast DNAs were detected: (i) perennial teosinte and Guatemala; (ii) Balsas and Huehuetenango; and (iii) all other teosintes. Four groups of mitochondrial DNAs were separated: (i) perennial teosinte; (ii) Guatemala; (iii) Nobogame; and (iv) all other teosintes. Separation of the teosinte and maize organelle DNAs into five groups (Guatemala; perennial teosinte; Balsas and Huehuetenango; Central Plateau and Chalco; Nobogame and maize) approximated the biosystematic relationships of the taxa. It was suggested that the evolutions of the chloroplast and mitochondrial DNAs may be independent of each other, that variation of organelle DNA within a species complex of an organism may be the common condition, and that the DNAs of the organelle and nuclear systems evolve in reasonable harmony.